Analysis of Business Processes and Performance of Manufacturing MSMES in Village Cileles Lebak Banten - Alfatih Sikki Manggabarani; Munasiron Miftah; Alfida Alfida (Yayasan Ilomata, 2021)
Business process analysis is a term that has a broad enough meaning for a.structere of different tactics such as simulation and diagnosis, verification and performance analysis of business processes This study aims to 1)analyze the business processes of manufacturing MSMEs ranging from production processes to marketing 2)How problems and constraints on business performance conditions now and in the future 3) What factors cause fluctuating performance of MSMEs , knowing what problems and constraints arise in the business process of MSMEs , 4) Knowing the size of the performance of MSMEs, analyzing the data and concluding the right problem solutions to improve the business processes of MSMEs and.utilizing information technology more maximally for the business processes of MSMEs. So that in the end, it can increase its income more maximally by itself can contribute to increase the income of rural communities. Considering that the village is still classified as a lagging village. The methods used to answer the problems in this study are Location Quotient Analysis (LQ), Descriptive Analysis, and SWOT Analysis. The result of LQ is known that in Kec.Cileles there are 6 sectors that are the base sector, namely agriculture, mining and quarrying, building, trading, home industry and restaurant, finance rental and corporate services, as well as other services, Then the absorption of labor dominant sector is in the processing industry sector. While swot results are known that the strategy that can be done is to maximize the potential of the industrial sector of holticulture product processing, improve the quality of human resources, and provide specifications on the type of superior products.